The Empowerment Strategy of The Traditional Fisherman’s Wives in The Coastal Area of Barru Regency, South Sulawesi - Abd. Rahim (Publisher of Widyagama University of Malang (UWG Press), 2018)
The policy of the Sarpras assistance program from the local government through the Office of Marine and Fisheries of Barru Regency has been conducted, but the income of traditional fisherman is not sufficient. Therefore, the role of wives is needed to fulfill the needs of the household. Research conducted in the Western Coastal Area of Barru Regency of South Sulawesi Province of Indonesia aims to analyze the empowerment strategy of traditional capture fisherman wives in order to improve the household economy. The type of research is a descriptive method with SWOT (Strength, Weakness Opportunities, and Threats) analysis technique through IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) and SWOT Matrix. Based on the time dimension using cross-sectional data of 2016 comes from the primary data. The samples of respondents were 34 traditional fishermen wives who worked in business groups in the sample districts by the census. The findings of the fishermen wives empowerment strategy can be done through strengthening coastal community institutions, access to capital, access to infrastructure and facilities, the technology of processing equipment, processed product modification technology, and marketing of processed fish products. JEL Classification: D10, D19, Q22